Learning and Teaching Together to Advance Evidence‐Based Clinical Education: A Faculty Learning Community. Issue 12 (1st December 2019) - Horvath, Zsuzsa; Washburn, Carol; Albrecht, Susan A.; Song, Meiyi; Meyer, Susan M.
Abstract : Clinical teaching is a cornerstone of health sciences education; it is also the most challenging aspect. The University of Pittsburgh Schools of Dental Medicine, Nursing, and Pharmacy developed a new evidence‐based interprofessional course framed as a faculty learning community (FLC) around the principles of learning in a clinical environment. The aim of this study was to assess the overall effectiveness of this two‐semester FLC at four health professions schools in academic year 2014‐15. The assessment included anonymous participant surveys in each session and an anonymous end‐of‐course survey. Thirty‐five faculty members from dental, health and rehabilitation sciences, nursing, and pharmacy enrolled in the FLC, with six to 32 enrollees attending each session. All attendees at each session completed the session evaluation surveys, but the attendance rate at each session ranged from 17.1% to 91.4%. Sixteen participants (46%) completed the end‐of‐course survey. The results showed overall positive responses to the FLC and changes in the participants' self‐reported knowledge. Session surveys showed that the participants found the FLC topics helpful and appreciated the opportunity to learn from each other and the interprofessional nature of the FLC. Responses to the end‐of‐course survey were in alignment with the individual session surveys and cited specific benefits as being the content, teaching materials, and structured discussions. In additional feedback, participants reported interest to continue as a cohort and to extend the peer‐support system beyond the FLC. This outcomes assessment of the first round of the FLC confirmed that this cohort‐based faculty development in an interprofessional setting was well received by its participants. Their feedback provided valuable insights for changes to future offerings.